Multi‐Charged Conjugated Polyelectrolytes as a Versatile Work Function Modifier for Organic Electronic Devices. (23rd September 2013) - Lee, Byoung Hoon; Jung, In Hwan; Woo, Han Young; Shim, Hong‐Ku; Kim, Geunjin; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> Despite the excellent work function adjustability of conjugated polyelectrolytes (CPEs), which induce a vacuum level shift via the formation of permanent dipoles at the CPE/metal electrode interface, the exact mechanism of electron injection through the CPE electron transport layer (ETL) remains unclear. In particular, understanding the ionic motion within the CPE ETLs when overcoming the sizable injection barrier is a significant challenge. Because the ionic functionality of CPEs is a key component for such functions, a rigorous analysis using highly controlled ion density (ID) in CPEs is crucial for understanding the underlying mechanism. Here, by introducing a new series of CPEs with various numbers of ionic functionalities, energy level tuning at such an interface can be determined directly by adjusting the ID in the CPEs. More importantly, these series CPEs indicate that two different mechanisms must be invoked according to the CPE thickness. The formation of permanent interfacial dipoles is critical with respect to electron injection through CPE ETL (≤ 10 nm, quantum mechanical tunneling limit), whereas electron injection through thick CPE ETL (20–30 nm) is dominated by the reorientation of the ionic side chains under a given electric field.